Changes in arterial K+ and ventilation during exercise in normal subjects and subjects with McArdle's syndrome. - David J. Paterson; Jon S. Friedland; Daphne A. Bascom; I Clement; D. A. Cunningham; Rosemary Painter; Peter A. Robbins (1990)
1. We have examined the relationship between ventilation (VE), lactate (La) and arterial plasma K+ concentrations [( K+]a) during incremental exercise in six normal subjects and in four subjects with McArdle's syndrome (myophosphorylase deficiency) who do not become acidotic during exercise. 2. In normal subjects, [K+]a rose to ca 7 mM at the point of exhaustion. The time courses of the increases in VE, La and [K+]a were all similar during the exercise period. La reached its peak concentration during the recovery from exercise when both VE and [K+]a were returning to resting levels. 3. McArdle's subjects, like normal subjects, had a non‐linear ventilatory response during incremental exercise. Their [K+]a was closely related to VE throughout exercise and recovery. 4. The arterial pH of McArdle's subjects, rather than remaining constant, actually rose from the onset of exercise. 5. For a given level of exercise, the levels of VE and [K+]a were greater in the McArdle's subjects than in normal subjects. 6. These findings are consistent with the idea that hyperkalaemia may contribute significantly to the drive to breathe, especially during heavy exercise.